PROBLEMATIKA IMPLEMENTASI PENDIDIKAN INKLUSIF: STUDI KASUS DI SD NEGERI KENAWA KABUPATEN LOMBOK TENGAH - Aldi Nurrasyid; Riza Dwi Lestari; Baiq Lilik Yulia Astuti; Faizah Habibatul Husna; Basilius Redan Werang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Inclusive education aims to provide equal educational opportunities for all students regardless of their backgrounds and learning characteristics. However, its implementation in regular elementary schools still faces various challenges. This study aims to analyze the implementation of inclusive education, identify the challenges encountered, and describe the school's efforts to address them at SD Negeri Kenawa, Central Lombok Regency. This study employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings indicate that SD Negeri Kenawa has implemented inclusive education by adapting learning strategies to students' diverse needs. The main challenges include the absence of a Special Assistant Teacher, limited supporting facilities, diverse student learning needs, and limited parental involvement. To address these challenges, the school has improved teacher competence through training, implemented adaptive learning strategies, and strengthened collaboration with parents. These findings highlight that successful inclusive education in regular schools requires adequate support, collaboration, and sustained commitment from all stakeholders.